2018
DOI: 10.1590/s1678-9946201860041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomphalaria sp. and other freshwater snails in the large-scale water transposition project in the Northeast of Brazil

Abstract: The wide eco-bio-social intervention generated by the SaoFrancisco River Integration Project (PISF) may contribute to the dispersion or introduction of schistosomiasis intermediate hosts in areas without prior recording. The objective was to characterize the limnic malacofauna and its distribution along watersheds involved in the PISF. A cross-sectional study based on the collection of mollusks from 33 water bodies, from Aurora, Brejo Santo, Jaguaretama, Jaguaribara, Jati e Mauriti municipalities in the Ceara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…Results obtained for species of freshwater and land mollusks which are medically relevant in the neotropics show the importance of combining traditional methods of morphological analysis with molecular methods to identify known species as well as potential cryptic species (Langand et al 1999, Campbell et al 2000, Dejong et al 2003, Wethington et al 2007, Teodoro et al 2010, Tuan et al 2012, Palasio et al 2017, Bezerra et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained for species of freshwater and land mollusks which are medically relevant in the neotropics show the importance of combining traditional methods of morphological analysis with molecular methods to identify known species as well as potential cryptic species (Langand et al 1999, Campbell et al 2000, Dejong et al 2003, Wethington et al 2007, Teodoro et al 2010, Tuan et al 2012, Palasio et al 2017, Bezerra et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the presence of bacteria in the aquatic environment may be related to the release of fresh domestic sewage into water bodies or the presence of feces from other homeothermic animals. Nevertheless, in other endemic areas in northeastern Brazil similar results were obtained and indicated the need for improvements in the basic sanitation system of those municipalities (48,54). Also, from their studies, it was concluded that there was a need to include results on E. coli contamination in spatial analyses to contribute to the determination of risk areas.…”
Section: Discussionmentioning
confidence: 69%
“…This snail species is the most successful and adapted to climate variation, it can be found in almost all Brazilian hydrographic basins (Terra et al, 2018). Despite being less susceptible to S. mansoni infection than B. glabrata (Bezerra et al, 2018), B. straminea has a wide distribution and is responsible for maintaining human infection rates above 50% in some locations in northeastern Brazil (Quinino et al, 2010;Neto et al 2012;Costa et al, 2017). B. straminea has previously been identified in 24 Brazilian states and usually inhabits temporary and permanent water collections, being more adjusted to the dry climate of the Northeast (Paula-Andrade et al, 2019;Ohlweiler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%